The value of an elastic tissue stain in detecting venous invasion in colorectal cancer. Issue 7 (25th June 2004) - Vass, D G; Ainsworth, R; Anderson, J H; Murray, D; Foulis, A K
Abstract : Background: Venous invasion by tumour is an independent prognostic indicator of both prognosis and risk of development of distant metastases in colorectal carcinoma. The use of special stains to aid its detection in pathology specimens is not currently universally recommended. Aims: To determine whether an elastica stain significantly increases the incidence of detection of vascular invasion compared with routinely stained sections. Methods: Serial sections from the 75 cases of colorectal carcinoma were stained by haematoxylin and eosin (H&E) only and elastica counterstained with H&E. The incidence of both intramural and extramural venous invasion was recorded and compared with that seen when the tumours were originally reported. Results: Extramural venous invasion had been noted in 14 of the pathology reports and was seen in 18 cases when only the H&E sections were viewed in the study. It was present in 32 cases when elastica stained sections were analysed. Intramural venous invasion was seen in eight cases on H&E sections and 30 cases on elastica stained sections. Conclusion: The use of elastica stained serial sections to detect venous invasion in tumours should be recommended in guidelines for the reporting of colorectal carcinomas.